TITANIC SURVIVAL PREDICTION USING MACHINE LEARNING - Kumari, Punita (Journal of Advanced Research in Signal Processing and Applications, 2024)
The sinking of the RMS [1] Titanic is without a doubt one of history's most notorious and horrifying catastrophes. The passenger ship Titanic, carrying 2224 people on board, sank on her maiden voyage and in the early hours of April 15, 1912, after striking with an iceberg, killing over 1502 of them. As a result, the ship was one of the deadliest commercial ships in history at the time. The legislation regulations controlling ship safety have been strengthened as a result of the horrible accident that rocked the world and left everyone feeling deeply sad and terrified. The structure's architect, Thomas Andrews, was killed in the accident. Following the sinking of the Titanic, it became clear that certain people had a better chance of survival than others. Priority had been given to children and women. The Titanic was a perfect illustration of its era, which was the beginning of the twentieth century and established a sharp divide in social strata. Exploratory data analytics (EDA) is utilised in the initial stages to discover truths that were previously concealed or unknown in the current data collection. Following the selection of multiple artificial intelligence and Machine Learning models, it is necessary to reach a conclusion regarding the study of which categories of people have a higher likelihood of survival. Following that, precision-based comparisons of the obtained machine learning models were performed.